DIASPORA AFRICA-BRAZIL & OF CANDOMBLÉ SPACE: SOME REFERENCES (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
One of the structural issues related to the African culture in Brazil that still deserves investigation and knowledge is related to the historiographic and geographic aspects of formation and distribution of the African descendent population in the Brazilian territory. This paper rescues the main references of the Africa-America-Brazil Diaspora and setsthe spatial expressionof someterreiros of candomblé in the city ofSalvador - Bahia.